Cucuran Darah dalam Ritual Pasola dan Makna Bagi Kehidupan Masyarakat Sumba - Kami, Kanisius; Artika, I Wayan; Artawan, Gede; Paramarta, I Ketut (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to describe the meaning of bloodshed in the Pasola ritual for people's lives in Sumba. This type of research is library research. The data in this research comes from books and scientific articles that discuss the Pasola ritual and its meaning. Data collection techniques are carried out through reading and analyzing literature relevant to the research topic. The data analysis technique is carried out through two main methods: first, content analysis, namely reviewing texts or documents to understand and interpret the meaning of the Pasola ritual; second, contextual analysis, namely understanding the social, cultural and historical context of the Pasola ritual. The results of this research found several important meanings of bloodshed in the Pasola ritual for the lives of the people of Sumba, including as a channel for fertility and successful harvests, respect for ancestors and guardian spirits of the land, as a ritual of purification and spiritual renewal, as a symbol of courage and virility, and a symbol of uniting society.